Diplodia corticola and Phytophthora cinnamomi : the main pathogens involved in holm oak decline on Caprera Island (Italy) - Linaldeddu, B. T.; Scanu, B.; Maddau, L.; Franceschini, A. (Forest Pathology, 2014)
Since 2008, severe and widespread tree decline and mortality has been observed at the main growing Quercus ilex L. (holm oak) forest on Caprera Island, Italy. To clarify the symptomatology and aetiology of this phenomenon, field surveys and isolations from symptomatic trees were carried out in summer 2010. Affected trees exhibited crown thinning, branch dieback, sunken cankers, epicormic shoots, exudates on branches and trunk, root losses and sudden death symptoms. Four fungal species belonging to Botryosphaeriaceae family, namely Botryosphaeria dothidea, Diplodia corticola, D. seriata and Neofusicoccum parvum, were isolated from cankers on trunk and branches, whereas three species of Phytophthora, namely P. cinnamomi, P. cryptogea and P. gonapodyides, were isolated from fine roots and rhizosphere soil samples. Isolates were identified using both morphological analysis and DNA-based techniques. Pathogenicity trials on holm oak seedlings showed that all the isolated species are pathogenic. D. corticola proved to be the most aggressive species. Our results provide the first evidence for a combined involvement of D. corticola and P. cinnamomi in the aetiology of holm oak decline in Italy and suggest that these pathogens are not only important contributing factors in the onset of long-term tree decline, but also may cause the rapid devastation of extensive oak ecosystems.
Key words by Adriana SilvaKey words by Adriana SilvaThe following values have no corresponding Zotero field: label: APS;Quercus ilex L.;fungus;mortality;pathogens;tree decline
Keywords: APS; Fungus; mortality; pathogens; Quercus ilex L.; tree decline

Influence of temperature on germination of Quercus ilex in Phytophthora cinnamomi , P. gonapodyides, P. quercina and P. psychrophila infested soils - Martín-García, J.; Solla, A.; Corcobado, T.; Siasou, E.; Woodward, S. (Forest Pathology, 2014)
The influence of temperature on germination of Quercus ilex acorns in Phytophthora infested soils was quantified for the first time. Radicle damage and mortality of Q. ilex seeds germinating at 17, 20, 23 and 26°Cin Phytophthora cinnamomi, P. gonapodyides, P. quercina and P. psychrophila infested soils were assessed and related to in vitro mycelium growth of the same isolates of the pathogens. The optimum growth temperatures of isolates of P. cinnamomi, P. gonapodyides, P. quercina and P. psychrophila were 20–23, 23–26, 20–23 and 20°C, respectively. At 17 and 20°C, all four Phytophthora species caused 100% acorn mortality, whereas at 26°C, acorn mortality was 100, 10, 25 and 0% in P. cinnamomi, P. gonapodyides, P. quercina and P. psychrophila infested soils, respectively. At 23°C, P. cinnamomi and P. gonapo- dyides reduced acorn radicle length more than P. quercina and P. psychrophila, whereas at 26°C, only P. cinnamomi caused further reduction in radicle length. The higher susceptibility of germinating acorns in comparison to seedlings reported in the literature indicates age-related susceptibility of Q. ilex to Phytophthora. The seedling/pathogen growth ratio was inversely related to the reduction in radicle length at different temperatures (R2 adj = 0.84, p < 0.0001), suggesting that rapid germination may allow seedlings to escape from infection. Increasing temperatures had different effects on damage to acorns depending on the pathogen present in the soil, indicating that Phytoph- thora species 9 temperature interactions determined Q. ilex germination. The effects of temperature on the impacts of Phytophthora spe- cies based on climate change predictions for Mediterranean countries are discussed.
Keywords: infected soils; phytophthora cinnamomi; Quercus ilex

First Report of Root Rot Caused by Pythium spiculum Affecting Cork Oaks at Donana Biological Reserve in Spain - De Vita, P.; Serrano, M. S.; Ramo, C.; Aponte, C.; Garcia, L. V.; Belbahri, L.; Sanchez, M. E. (PLANT DISEASE, 2013)
APSAPSThe following values have no corresponding Zotero field: pub-location: 3340 PILOT KNOB ROAD, ST PAUL, MN 55121 USA publisher: AMER PHYTOPATHOLOGICAL SOC
Keywords: Cork oak; Donana Biological Reserve; Pythium spiculum; Spain

Pathogenicity of Pythium spiculum and P-sterilum on feeder roots of Quercus rotundifolia - Jimenez, J. J.; Sanchez, J. E.; Romero, M. A.; Belbahri, L.; Trapero, A.; Lefort, F.; Sanchez, M. E. (PLANT PATHOLOGY, 2008)
APSAPSThe following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: pathogenic; Pythium spiculum; Pythium sterilum; Quercus ilex